Evaluation of the Relationship Between Pars Interarticularis Defect with Subcutaneous Fat Thickness and Abdominal Circumference - Mehmet Şirik; İbrahim İnan (Van Tıp Dergisi, 2018)
INTRODUCTION: To evaluate the relationship between subcutaneous fat tissue thickness and abdominal circumference increase with pars interarticularis defect. METHODS: We retrospectively reviewed the images of patients who underwent abdominopelvic computed tomography (CT) in our department due to various clinical indications between January 2017 and June 2017. Sixty-six patients with pars interarticularis defect (PIAD) and 69 randomly selected patients with normal CT findings were included in the study. Subcutaneous fat thickness (SFT) and abdominal circumference (AC) were measured on axial CT images of all patients. The relationship between presence of PIAD with subcutaneous fat thicknesses and abdominal circumference was statistically analyzed. RESULTS: Of the 135 cases included in the study, 67 (49.6%) were female and 68 (50.4%) were male. The mean SFT value was 28.4 +- 9.68 mm, the average of abdomen circumference was 96.3 +- 13 cm. The mean SFT values were higher in women than in men (p <0.001). Age and AC were significantly different between cases with PIAD and without PIAD (p <0.001). In cases with PIAD, AC and age were higher than cases without PIAD. DISCUSSION AND CONCLUSION: Development of the pars interarticularis defect correlates with age and abdominal circumference. Increase of the abdominal circumference is an indication of obesity. We believe that PIAD should be kept in mind in order to prevent serious complications that may develop secondary to PIAD and to take preventative measures such as weight control since the progress of age together with obesity because of the increases the risk of developing PIAD.